Mayaro Virus Replication Restriction and Induction of Muscular Inflammation in Mice Are Dependent on Age, Type-I Interferon Response, and Adaptive Immunity - Figueiredo, Camila Menezes; Neris, Romulo Leão da Silva; Gavino-Leopoldino, Daniel; da Silva, Mariana Oliveira Lopes; Almeida, Juliana Silva; dos-Santos, Julio Souza; Figueiredo, Claudia Pinto; Bellio, Maria; Bozza, Marcelo Torres; Assunção-Miranda, Iranaia (Frontiers in Microbiology, 2019)
Mayaro virus (MAYV) is an emergent arbovirus first described in forest regions of the American continent, with recent and increasing notification of urban area circulation. Similar to Chikungunya (CHIKV) and other arthritogenic Alphavirus, MAYV-induced disease shows a high prevalence of persistent arthralgia, and myalgia. Despite this, knowledge regarding pathogenesis and characteristics of host immune response of MAYV infections are still limited. Here, using different ages of wild-type (WT), adult Type I Interferon receptor deficient (IFNAR–/–), and adult recombination activation gene-1 deficient (RAG–/–) mice, we have investigated the dependence of age, innate and adaptive immunity for the control of MAYV replication, tissue damage, and inflammation in mice. We have found that MAYV induces clinical signal and replicates in young WT mice, which gain the ability to restrict MAYV replication with aging. In addition, we observed that mice age and type I interferon response are related to restriction of MAYV infection and muscular inflammation in mice. Moreover, MAYV continues to replicate persistently in RAG–/– mice, being detected at blood and tissues 40 days post infection, indicating that adaptive immunity is essential to MAYV clearance. Despite chronic replication, infected adult RAG–/– mice did not develop an apparent signal of muscle damage in early and late infection. On the other hand, MAYV infection in young WT and adult IFNAR-/- mice triggers an increase in the expression of pro-inflammatory mediators, such as TNF, IL-6, KC, IL-1β, MCP-1, and RANTES, in muscle tissue, and decreases TGF-β expression, that were not significantly modulated in adult WT and RAG–/– mice. Taken together, our data demonstrated that age, innate and adaptive immunity are important to restrict MAYV replication and that adaptive immunity is also involved in MAYV-induced tissue damage. These results contribute to the comprehension of MAYV pathogenesis, and describe translational mice models for further studies of MAYV infection, vaccine tests, and therapeutic strategies against this virus.